2011
DOI: 10.1038/onc.2011.556
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty1 is a candidate tumor-suppressor gene in medullary thyroid carcinoma

Abstract: Medullary thyroid carcinoma (MTC) is a malignancy derived from the calcitonin-producing C-cells of the thyroid gland. Oncogenic mutations of the Ret proto-oncogene are found in all heritable forms of MTC and roughly one half of the sporadic cases. However, several lines of evidence argue for the existence of additional genetic lesions necessary for the development of medullary thyroid carcinoma. Sprouty (Spry) family of genes is composed of four members in mammals (Spry1-4). Some Spry family members have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 52 publications
(63 reference statements)
0
35
0
Order By: Relevance
“…On the other hand, circulating T3 and T4 levels were virtually identical between genotypes, indicating that thyroids from Spry1 knockout mice are euthyroid (Figures 2c and d). These data, together with high Spry1 levels found in mouse thyroid with respect to other organs, 8 suggested that Spry1 directly influences the proliferation of follicular cells in a cell-autonomous manner. To further support this notion, we isolated follicles from 3-month-old mice of both genotypes and found that follicular cells from mutant mice proliferated faster in vitro, as measured by 5 0 -bromo-deoxyuridine uptake (Figure 2f).…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…On the other hand, circulating T3 and T4 levels were virtually identical between genotypes, indicating that thyroids from Spry1 knockout mice are euthyroid (Figures 2c and d). These data, together with high Spry1 levels found in mouse thyroid with respect to other organs, 8 suggested that Spry1 directly influences the proliferation of follicular cells in a cell-autonomous manner. To further support this notion, we isolated follicles from 3-month-old mice of both genotypes and found that follicular cells from mutant mice proliferated faster in vitro, as measured by 5 0 -bromo-deoxyuridine uptake (Figure 2f).…”
Section: Resultsmentioning
confidence: 82%
“…We have previously shown that Spry1 knockout mice exhibit thyroid C-cell hyperplasia. 8 While examining the number of C-cells, we noticed that thyroids from 3 months old Spry1 knockout mice, although having normal shape and showing no external signs of malignant growth, were bigger than those from wild-type littermates (Figure 1a). To confirm these observations, we estimated the thyroid lobe size from 3 months old wild-type and Spry1 null littermates.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations